หลักการพัฒนาชุดตรวจแบบแถบสีชนิดรู้ผลรวดเร็ว และแนวทางการปรับปรุง - สิทธิกรกุล ไพศาล; หวังมาน ประดิษฐ์; ลงยันต์ ศิวาพร; ชัยวิสุทธางกูร ปรินทร์ (Science Essence Journal, 2017)
บทคัดย่อ ชุดตรวจแบบแถบสี (Lateral flow immunochromatographic strip tests: LFICS) เป็นชุดตรวจที่ทำงานโดยการแยกสารที่ต้องการตรวจออกจากสารผสม ร่วมกับปฏิกิริยาระหว่างแอนติบอดีกับแอนติเจน หรือระหว่างกรดนิวคลีอิก บนเมมเบรนสำหรับใช้ตรวจสอบสารต่างๆ เช่น ฮอร์โมน เปบไทด์ เครื่องหมายมะเร็ง จุลินทรีย์ และสารพิษ ชุดตรวจประเภทนี้มีข้อดีหลายประการ เช่น ค่าใช้จ่ายต่ำ ใช้ง่ายโดยไม่ต้องอาศัยความชำนาญ ทำได้นอกสถานที่และทราบผลรวดเร็ว หลักการทำงานของชุดตรวจแบบแถบสี 3 รูปแบบหลักที่ใช้อนุภาคนาโนทองคำเป็นตัวแสดงผล คือ sandwich, competitive และแบบตรวจแอนติบอดี ชุดตรวจแบบแถบสีมีข้อจำกัดในแง่ความไวซึ่งขึ้นกับแรงจับของแอนติบอดี การรวมปฏิกิริยา polymerase chain reaction รูปแบบต่างๆ กับชุดตรวจทำให้สามารถตรวจสอบสิ่งมีชีวิตต่างๆ ด้วยความไวสูงและทราบผลเร็วขึ้น การปรับปรุงชุดตรวจเพื่อเพิ่มความไวในรูปแบบต่างๆ ได้แก่ double gold labeling, silver enhancing, enzyme labeling หรือแทนที่อนุภาคนาโนทองคำด้วยสารต่างๆ เช่น carbon nanotube, carbon nanoparticle, quantum dot และ magnetic nanoparticle เป็นต้น การปรับปรุงเหล่านี้อาจต้องใช้เครื่องอ่านและวิเคราะห์ผลเพิ่มขึ้น แต่ด้วยเทคโนโนยีของโทรศัพท์เคลื่อนที่ อาจปรับปรุงให้สามารถใช้ร่วมกับชุดตรวจ ซึ่งจะช่วยให้การใช้ชุดตรวจแบบแถบสีสำหรับตรวจสิ่งต่างๆ ทำได้กว้างขวาง Rapid Lateral Flow Immunochromatographic Strip Tests (LFICS): Principle and Modifications Abstract Lateral flow immunochromatographic strip tests (LFICS) is a chromatographic system based on separation of analyte in the mixture through the reaction between antibody and antigen or between nucleic acids on the membrane. LFICS has been developed for detection of various molecules such as hormones, peptides, cancer markers, microorganism, toxins, drugs, pesticides, etc. LFICS has many advantages in terms of low cost, rapid and visual results. The operation is simple and can be performed on site by unskilled personnel with low cost and minimal labor. Principles of three formats including sandwich, competitive and antibody detection LFICSs using nanogold particles as reporter are described. The detection sensitivity of LFICS is mainly limited by antibody affinity. Different types of polymerase chain reactions have been combined successfully with LFICS for highly sensitive and rapid detection of PCR products from various organisms. Other modifications of LFICS using dual gold labeling, silver enhancing, enzyme labeling or replacement of nanogold particle with carbon nanotube, carbon nanoparticle, quantum dot and magnetic nanoparticle are promising tools to increase the sensitivity of LFICS. Even though, some modifications may need additional strip reader and analytical equipment, the improvement of mobile phone technology would assist the widely use of LFICS for detection of various molecules.